HOW CRUCIAL IS THE WORKING ENVIRONMENT IN SUPPORTING THE PERFORMANCE OF HEALTH WORKERS? - Nuzulul Kusuma Putri (Universitas Airlangga, 2021)
In the last semester of the second year of the COVID-19 pandemic, our journal emphasizes its current issue on the life of health workers as humans. We choose to underline the working environment condition as one of the super significant predictors of health workers’ performance, leading to a stronger health system in the future.